Mathematical modeling process of liquid filtration taking into account reverse influence of process characteristics on medium characteristics - Safonyk, Andrii; Bomba, Andrii (International Journal of Applied Mathematical Research, 2014)
The article presents and solves the questions of accounting for reverse influence of process characteristics (the contamination concentration of liquid and sediment) on medium characteristics (the coefficients of porosity, filtration, diffusion, mass-transfer and others) by the example of liquid cleaning in magnetic and sorption filters. The algorithm of numerical-asymptotic approximation to the solution of the relevant model task which is described by the system of nonlinear singular perturbative differential equations of the type «convection-diffusion-mass-transfer». The proper correlations (formulas) are effective for conducting theoretical researches which are aimed at the «productivity» (in particular, optimization) of the parameters of filtration process (namely: time of protective action of load, sizes of filter, and others) in cases of predominance of convection and sorption components of the proper process above diffusive and desorption components, that takes place in large majority of filtration installations. The computer experiment was conducted on this basis. These ones results show the advantages of the offered model in comparing to classic.